Fabrication of Alginate-Based Electrospun Nanofibers for Carbon Dioxide Removal - Adhitasari Suratman; Desi Nur Astuti; Ryan Jonathan; Agus Kuncaka; Yusril Yusuf (Universitas Gadjah Mada, 2022)
A fabrication of eco-friendly and low-cost adsorbent materials is reported for CO2 removal. Alginate nanofibers (NFs) adsorbents were prepared by incorporating poly(vinyl alcohol) (PVA) into alginate solutions via electrospinning technique from alginate biopolymers. Smooth-surfaced Alg/PVA NFs were obtained with a specific surface area of 9.197 m2 g–1. Zeolite (Z) was impregnated into polymer solutions to enhance the properties and performances of alginate nanofibers. Alg/PVA/Z NFs appeared to be rougher with a specific surface area of 25.998 m2 g–1. Both adsorbents offered great potential for CO2 adsorbent in the future. The adsorption isotherms of Alg/PVA NFs followed the Langmuir model with optimum CO2 adsorption capacity of 3.286 mmol g–1 and Alg/PVA/Z NFs followed Dubinin-Radushkevich model with optimum CO2 adsorption capacity of 10.710 mmol g–1.